Physical and Dosimetric Aspects of the Iridium-Knife - Roussakis, Yiannis; Anagnostopoulos, Georgios (Frontiers in Oncology, 2021)
The three-dimensional iridium-192 (192Ir) high-dose-rate (HDR) brachytherapy manifests itself as a high precision, hypo-fractionated, dose-escalating, minimally invasive method in the armamentarium of the contemporary Radiation Oncology clinical applications. In this study, the physical aspects of the 192Ir radionuclide are presented. Its dosimetric application in the HDR brachytherapy for different anatomical sites (prostate, gynecological malignancies, liver, and intrathoracic tumors) as well as the corresponding dosimetric comparison with the stereotactic body radiation therapy (SBRT) techniques based on a representative selection of dosimetric publications is reviewed and illustrated.